Caracterização Anatômica de Cinco Espécies do Gênero Cordia L. (Boraginaceae), ocorrentes na Amazônia Brasileira, para Melhor Utilização pelo Mercado Madeireiro de Paragominas, Pará - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2007)
The municipality of Paragominas stands out as one of the poles of greatest timber aptitude in the state of Pará, both for its location and for its forest variability. However, due to the similarities, species of high economic value are exchanged for others of inferior quality. In this context, the anatomical study is a tool of vital importance for the timber trade, because it provides sellers and buyers with the guarantee that they need regarding the real identification of the species and transparency in the transaction. The present work aims to macroscopically characterize five species of Cordia, known as Freijó, and to elaborate an identification key to assist the species studied. The macroscopic description followed the traditional methodology used for studies in wood anatomy. The materials examined were Cordia alliodora Cham, C. bicotor A.DC, C. goeldiana Huber, C. scabrida Mart, C. tetranda Aubl obtained from the Xilotheque "Walter Egler" collection of the Museu Paraense Emílio Goeldi. Through macroscopic analysis the species were separated according to the type of parenchyma, visibility of the rays in cross section and grouping of the pores. C. alliodora Cham, C. goeldiana Huber and C. tetranda Aubl showed a predominance of vasicentric paratracheal parenchyma and visible rays under a 10x lens. In C. bicotor A.DC it was possible to observe scarce parenchyma and rays invisible under a 10x lens. As for the grouping of the pores, with the exception of C. tetranda Aubl with multiples of two and rare multiples of three, the other species presented predominantly solitary arrangement. From the results obtained, it is concluded that the species studied can be separated through their macroscopic anatomical characteristics.
Anatomical Characterization of Five Species of the Cordia L. genus (Boraginaceae), occurring in the Brazilian Amazon, for Better Utilization by the Timber Market of Paragominas, Pará
Keywords: Anatomia; Macroscópica; Cordia; CNPQ::CIENCIAS BIOLOGICAS::BOTANICA::MORFOLOGIA VEGETAL::ANATOMIA VEGETAL